Ethnobotany of the apricot tree (Prunus armeniaca L.) in the Batna Region, Algeria: Traditional knowledge, uses, and socio-economic importance - Laabassi, Ayache; Fercha, Azzedine; Chafaa, Smail; Mimeche, Fateh (Ethnobotany Research and Applications, 2026)
Background: The apricot tree (Prunus armeniaca L.) is deeply embedded in the agricultural and cultural traditions of the Batna region in northeastern Algeria. It holds significant economic value and is associated with a rich body of traditional knowledge, encompassing a wide range of uses that remain largely undocumented and are at risk of being lost. Methods: Ethnobotanical surveys were conducted from March 2023 to August 2024 in 15 Batna municipalities. Data were collected from 150 local informants using semi-structured interviews and participant observation. Quantitative data were interpreted using ethnobotanical indices such as Use Value (UV), Fidelity Level (FL%), and Informant Consensus Factor (ICF). Results: Prunus armeniaca is a versatile species with profound socio-economic and cultural value in the Batna region. A total of 28 distinct uses were recorded, distributed across four categories: food (56% of use-reports), medicinal (25%), handicraft (11%), and fodder (8%). All parts of the tree are utilized, with the fruit being the most commonly used (92% of informants). Quantitative indices revealed a high overall Use Value (UV = 0.89) and a significant knowledge gap between older and younger generations (p < 0.001). Conclusions: This study provides a crucial baseline record of the traditional knowledge associated with P. armeniaca and highlights the urgent need for its conservation in light of the observed intergenerational knowledge erosion. The findings underscore the species’ integral role in local livelihoods and identify potential for developing sustainable value-added products, that could support local economies and help preserve this intangible cultural heritage. Key words: Ethnobotany; Prunus armeniaca, Traditional Knowledge; Quantitative Indices, Batna; Algeria, Conservation